Effect of solid waste landfill leachate contaminants on hydraulic conductivity of landfill liners - Ozcoban, Mehmet Sukru; Acarer, Seren; Tufekci, Nese (IWA PUBLISHING, 2022)
Landfilling is one of the most widely used methods to reduce the impact on the environment and human health by ensuring the management of solid wastes. For the process in question to be called landfill, the landfill leachate must be controlled and liner impermeability conditions must be provided. For this reason, compacted clay liners (CCL) and geosynthetic clay liners (GCL) with very low hydraulic conductivity are often used as hydraulic barriers in landfills to prevent the risk of leachate mixing with groundwater. However, as a result of various interactions between leachate-clay liners, changes occur in the hydraulic conductivity of the liners. In this review, the change (increase/decrease) in the hydraulic conductivity of the landfill liners caused by the contaminants in the leachate composition and the mechanisms responsible for this change were examined. In addition, deficiencies in the literature on this subject were identified and directions for future studies were presented.
Keywords: clay liner; hydraulic conductivity; landfill; leachate; GEOSYNTHETIC CLAY LINERS; SELF-HEALING CAPACITY; COMPACTED CLAY; SUSPENDED-SOLIDS; POROUS-MEDIA; GEOTECHNICAL PROPERTIES; CHEMICAL-PROPERTIES; BENTONITE MIXTURES; PERMEABILITY; SOILS; Engineering; Environmental Sciences & Ecology; Water Resources